Dampak Kurangnya Motivasi Siswa SD/MI Terhadap Perkembangan Sosioemosional - Rachma , Lupita Atika; Afifah, Nur; Rizqi Ramadhani, Irnawan; Munawaroh, Hidayatu (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2023)
Motivation as a motivating factor to take an action and say a word, caused by an environmental situation that is less supportive as well as worry about making mistakes can eliminate this motivation completely. This study aims to determine the impact of lack of motivation of elementary / Madrasah Ibtidaiyah students on socioemotional development so as to determine solutions to prevent it. The method used is a qualitative approach that will produce descriptive data. The object of this study is the socioemotional development of elementary / MI students. Data were taken using interview techniques as the main data and observation as complementary data. From this study it is known that intrinsic and extrinsic motivation has a great impact on the socioemotional development of students. If this motivation is lacking or hampered by factors that come from within students or even from their unsupportive environment, it will result in loss of curiosity, lack of confidence, difficulty adapting, and choosing to be alone rather than looking for peers. Even though this is part of the socioemotional development of students that needs to be passed from childhood.